2015
DOI: 10.2169/internalmedicine.54.3057
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Alveolar Hemorrhage with Predominantly Right-sided Infiltration Resulting from Cardiac Comorbidities

Abstract: Objective Radiographic findings in patients with diffuse alveolar hemorrhage (DAH) are usually diffuse and bilateral, although they may occasionally be unilateral. The clinical aspects of predominantly unilateral DAH are not well known. Therefore, our objective was to describe the clinical characteristics of predominantly right-sided DAH. Methods We retrospectively reviewed data for 460 bronchoalveolar lavage fluid (BALF) samples collected between January 2009 and July 2013. Patients who presented with increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Unilateral DAH is rare and is occasionally accompanied by heart failure, clotting disorder, and pneumonia. In a previous report, right‐sided DAH was frequently caused by pulmonary congestion resulting from heart failure 9 …”
Section: Discussionmentioning
confidence: 94%
“…Unilateral DAH is rare and is occasionally accompanied by heart failure, clotting disorder, and pneumonia. In a previous report, right‐sided DAH was frequently caused by pulmonary congestion resulting from heart failure 9 …”
Section: Discussionmentioning
confidence: 94%
“…Approximately 90% of these patients had right-sided infiltrate [11]. As data regarding the occurrence of UDAH are scarce (mostly in the form of case reports), a diagnosis is often delayed or even missed, as was the case for our patient [12]. The following mechanisms have been proposed as the possible explanation for the preferential occurrence of right-sided DAH: (i) Directionality of the regurgitant flow: Severe mitral regurgitation is often present in this patient population.…”
Section: Discussionmentioning
confidence: 71%
“…This can occur in patients with an accessory RML pulmonary vein that drains to the left atrium in a venous confluence with RUL pulmonary vein. Unilateral infiltrate involving the left upper lobe has also been reported [12]. (ii) Inadequate lymphatic drainage of the right lung: the lymphatic drainage of the right and left lungs is accomplished by the right broncho-mediastinal trunk and thoracic duct, respectively.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Chronic heart failure increases pulmonary venous pressure, which might induce micro-vessel rupture, resulting in DAH ( 13 , 14 ). Interestingly, a recent study showed that cardiovascular diseases increased long-term mortality in patients with DAH ( 15 ), which is indicative of a close pathophysiologic relationship between them.…”
Section: Discussionmentioning
confidence: 99%